2012
DOI: 10.1593/tlo.12109
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Magnetic Resonance Imaging for Investigating the Development and Distribution of Experimental Brain Metastases due to Breast Cancer

Abstract: There was no difference in the mean number of metastases for either cell line. The volumes of metastases in mice injected with 231-BR-HER2 cells were significantly larger than those for mice injected with 231-BR cells. The growth rate for 231-BR-HER2 metastases was 67.5% compared with 54.4% for the 231-BR metastases. More than 50% of metastases were located in the cortex and 25% to 30% of metastases were identified in the central brain for each time point and for mice injected with either cell line. The volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…Moreover, the observed BTB permeability at different locations within the brain did not appear to influence permeability in these models supporting previous MRI studies examining the distribution of gadolinium-enhancing metastases in similar preclinical models [19]. The brain distribution of metastatic foci in each model presented herein appear consistent with similar studies demonstrating more than 50% of metastatic burden occurs in cortical regions, with relatively fewer lesions occurring in the central brain regions, and the least metastatic growth observed in the posterior and olfactory regions [47,48]. Additionally, this work agrees with previous findings [46] suggesting the presence of HER2 does not seem to correlate strongly with changes in vascular permeability (permeability of JIMT-1-BR3, SUM190-BR3, and MDA-MB-231BR-HER2+ lines were not congruent) and that permeability changes appear to be more cell line specific (i.e., MDA-BB-231BR and MDA-MB-231BR-HER2+).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the observed BTB permeability at different locations within the brain did not appear to influence permeability in these models supporting previous MRI studies examining the distribution of gadolinium-enhancing metastases in similar preclinical models [19]. The brain distribution of metastatic foci in each model presented herein appear consistent with similar studies demonstrating more than 50% of metastatic burden occurs in cortical regions, with relatively fewer lesions occurring in the central brain regions, and the least metastatic growth observed in the posterior and olfactory regions [47,48]. Additionally, this work agrees with previous findings [46] suggesting the presence of HER2 does not seem to correlate strongly with changes in vascular permeability (permeability of JIMT-1-BR3, SUM190-BR3, and MDA-MB-231BR-HER2+ lines were not congruent) and that permeability changes appear to be more cell line specific (i.e., MDA-BB-231BR and MDA-MB-231BR-HER2+).…”
Section: Discussionsupporting
confidence: 87%
“…injected 5 × 10 5 SUM190-BR3 cells compared to 1.75 × 10 5 cells used to initiate our model. Similarly, number of cells injected has been previously shown to affect the number of metastases in preclinical brain metastases models [47,49]. Despite the observed differences in relative lesion sizes and the reported sizes of SUM190-BR3 by Murrell et al, we observed similar survival patterns as those reported by their group.…”
Section: Discussionsupporting
confidence: 86%
“…We performed the study in two mouse models of triple-negative breast cancer brain metastasis: the nu/nu mouse MDA-MB-231BR model [17, 18, 21, 22] and the BalbC mouse 4T1-BR5 model. In the 231BR model, the blood-brain barrier (BBB) has previously been shown to remain intact in early stages of disease progression [17]; thus, to be effective, any therapeutic applied early in the course of development needed to be able to traverse an intact BBB.…”
Section: Discussionmentioning
confidence: 99%
“…The asterisks denote a statistically significant difference (P <0.05) between the two cell lines. Adapted with permission from Perera et al [45] increase in signal intensity (enhancement) of the tumor in the post-Gad image. Since longitudinal imaging can be performed with MRI, it provides an excellent tool for investigating tumor growth and responses to treatment over time.…”
Section: Clinical Mri For Brain Metastasesmentioning
confidence: 99%
“…Perera et al used MRI to compare the growth of 231BR and 231BR-HER2 brain metastases [45]. The number of Fig.…”
Section: Clinical Mri For Brain Metastasesmentioning
confidence: 99%